Marketing strategy at e-commerce Double-Six Luxury Hotel Seminyak to maximize room occupancy - Ni Putu Ayu Vena Aryanthi; Gede Pradiva Adiningrat; Upayana Wiguna Eka Saputra (Journal of Applied Sciences in Travel and Hospitality, 2023)
The E-Commerce division at Double-Six Luxury Hotel Seminyak has an important role in selling rooms through websites and OTA platforms. Given the shift caused by the Covid-19 pandemic, where the majority are now leaning towards booking rooms online, recalibrating strategies to fit the new normal era has become imperative for this division. This research seeks to identify potential internal and external factors affecting the E-Commerce unit and formulate marketing strategies to increase room occupancy rates. Qualitative and quantitative data were collected from primary and secondary sources. For the initial research questions, methodologies such as observation, interviews, and document review were used. IFAS and EFAS matrices were developed using a questionnaire, while IE and SWOT matrices were developed based on a literature review. The research also proposed a strategic approach rooted in a combination of internal and external factors. Using purposive sampling, the findings emphasize the importance of internal factors such as the elements of the marketing mix-product, price, place, promotion, people, process, and physical evidence. As well as the importance of considering external factors such as customers, competitors, distributors, and the public practically, these insights suggest that Double-Six Luxury Hotel Seminyak's E-Commerce unit should consider a growth-oriented approach. This entails pursuing vertical integration with direct room sales through hotel’s website, creating stay packages with additional benefits, creating customer data-driven pro-motions, and increasing website visibility through SEM and SEO.